A RESEARCH ON VARIABLES OF ROLE EFFICACY INFLUENCING OPINION OF PRODUCTION ENGINEERS BASED ON EXPERIENCE - Evangeline, C.; Asir, G. Samuel Arul; Shameem, A. (International Journal of Psychosocial Rehabilitation, 2020)
Role efficacy being a psychological concept deals with the effectiveness of an individual why may be positioned in any specific role in an organisation. In order to be able to make an employee contribute his or her fullest level of competence, it becomes important for the role to provide that motivation if the role occupied by the employee fails to be motivating it could ultimately result in frustration with work which in turn is bound to reduce the employee’s productivity drastically thereby leading to reduction in employee’s effectiveness. This study has been undertaken to identify the different variables of self-efficacy and to identity the relationship between the variables of role efficacy and experience of production engineers in Chennai. The results of the study have shown that that there is significant difference between experience of production executives and all the variables influencing role efficacy.